2022
DOI: 10.1021/acsami.2c11634
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanoarchitectonics of Hollow Mesoporous Copper Oxide-Based Nanozymes with Cascade Catalytic Reaction for Near Infrared-II Reinforced Photothermal-Catalytic Therapy

Abstract: Biomimetic nanozyme with natural enzyme-like activities has drawn extensive attention in cancer therapy, while its application was hindered by the limited catalytic efficacy in the complicated tumor microenvironment (TME). Herein, a hybrid biomimetic nanozyme combines polydopamine-decorated CuO with a natural enzyme of glucose oxidase (GOD), among which CuO is endowed with a high loading rate (47.1%) of GOD due to the elaborately designed hollow mesoporous structure that is constructed to maximize the cascade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
0
16
1
Order By: Relevance
“…With the action of oxygen and GOx, glucose can be converted into gluconic acid and H 2 O 2 , thereby cutting off the nutrition source of tumor cells and inhibiting cancer cell proliferation ( Huo et al, 2017 ; Xu et al, 2022c ; Wang et al, 2022f ). Considering that the catalytic activity of a single enzyme is insufficient to achieve satisfactory therapeutic effects, the development of nanozymes with multiple enzyme-mimetic functions is necessary.…”
Section: Nanomaterial-mediated Tumor Hypoxia Reliefmentioning
confidence: 99%
“…With the action of oxygen and GOx, glucose can be converted into gluconic acid and H 2 O 2 , thereby cutting off the nutrition source of tumor cells and inhibiting cancer cell proliferation ( Huo et al, 2017 ; Xu et al, 2022c ; Wang et al, 2022f ). Considering that the catalytic activity of a single enzyme is insufficient to achieve satisfactory therapeutic effects, the development of nanozymes with multiple enzyme-mimetic functions is necessary.…”
Section: Nanomaterial-mediated Tumor Hypoxia Reliefmentioning
confidence: 99%
“…To further imitate temperature variations caused by the photothermal effect of HMMSNs nanozymes, the reaction solutions were kept at 37 °C (control) and 51 °C (photothermal group). [ 42 ] As revealed by the UV–vis absorption curves in Figure 4b, a notable drop in MB absorbance at 51 °C confirmed that the NIR‐II‐induced hyperthermia will enhance POD‐like effect of HMMSNs. Meanwhile, the degradation of MB was also promoted as the GSH and H 2 O 2 levels increased from 0 to 10 mM under weakly acidic condition (Figure S17a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 77%
“…Wang et al designed and synthesized a hollow mesoporous copper oxide (HMC), loaded substantial GOD, and modified with polydopamine for the enhancement of hydrophilicity and biocompatibility (HMCGP). 224 At the hypoxic tumor site, the HMCGP could produce O 2 by decomposition of H 2 O 2 to alleviate the tumor hypoxia and enhance the catalytic activity of GOD. Meanwhile, the oxidation of glucose-induced decline of pH and increase of H 2 O 2 can induce a cascade enzyme reaction to maximize the catalytic efficiency of HMCGP.…”
Section: Hypoxia-relieving Strategies Based On Nanomedicinementioning
confidence: 99%
“…Metal oxide nanoenzymes, such as CuO, MnO 2 , and CeO 2 , are promising in catalyzing the O 2 production reaction of endogenous H 2 O 2 to relieve tumor hypoxia. Wang et al designed and synthesized a hollow mesoporous copper oxide (HMC), loaded substantial GOD, and modified with polydopamine for the enhancement of hydrophilicity and biocompatibility (HMCGP) . At the hypoxic tumor site, the HMCGP could produce O 2 by decomposition of H 2 O 2 to alleviate the tumor hypoxia and enhance the catalytic activity of GOD.…”
Section: Hypoxia-relieving Strategies Based On Nanomedicinementioning
confidence: 99%